Extraction of essential oil from Nigella sativa using supercritical carbon dioxide : study of antibacterial activity. - Abdullah Al-Haj, Nagi Ahmed; Shamsudin, Mariana Nor; Zamri, Hana Farizah; Abdullah, Rasedee (Science Publications, 2008)
The antimicrobial activity of N. sativa essential oil obtained by supercritical fluid extraction by carbon dioxide was investigated against Gram Positive and Gram negative strains, isolated from clinical specimens. Best conditions for Black cumin oil extraction are obtained at 400 bar, 40°C and a solvent flow rate of 25 g min-1. The seed extracts were prepared by supercritical fluid extraction method. Filter paper discs impregnated with varying concentrations of N. sativa extract were tested by the disk diffusion method. Methicillin Resistant Staphylococcus Aureus (MRSA) ATCC strain (700968), E. coli ATCC strain (25922), E. coli 0157 ATCC strain (12799), Extended-Spectrum Beta-Lactamase (ESBL) Klebsiella pneumoniae ATCC strain (700603), Carbapenam Resistant acenitobacter Baumanii (CRAB) clinical strain and Vibrio cholerae 01 Ogawa and 0139 Bengal clinical strains were investigated. The inhibition zones of the Mueller Hinton agar in different extract concentrate ion showed that at 25 mg 20 μL-1, 50 mg 20 μL-1 and 100 mg 20 μL-1, the inhibition zones increased accordingly in S. aureu. However, N. sativa was found to be inactive against ESBL producers (E. coli and K. pneumoniae).